2013
DOI: 10.1021/bi400103t
|View full text |Cite
|
Sign up to set email alerts
|

The Lipid Bilayer-Inserted Membrane Protein BamA of Escherichia coli Facilitates Insertion and Folding of Outer Membrane Protein A from Its Complex with Skp

Abstract: Folding of β-barrel membrane proteins, either from a urea-unfolded form or from chaperone-bound aqueous forms, has been characterized for pure lipid bilayers. The impact of preinserted integral proteins from biomembranes has not been examined in biophysical comparisons, but this knowledge is important for the characterization of protein assembly machinery in membranes to distinguish specific effects from unspecific effects. Here, folding was studied for a β-barrel membrane protein, outer membrane protein A (Om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
85
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(101 citation statements)
references
References 77 publications
15
85
1
Order By: Relevance
“…Previous studies have shown that BamA alone accelerates the folding of OmpA and other empty b-barrel proteins including OmpX and OmpLA into LUVs that contain PG or a small amount of PE (20%), but only at high pH (34,36). Furthermore, even in the presence of BamA, the assembly of OMPs into liposomes composed purely of neutral PC lipids was faster and more efficient, and BamA relieved the inhibitory effect of lipid head groups on the assembly of some proteins more effectively than others (34).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that BamA alone accelerates the folding of OmpA and other empty b-barrel proteins including OmpX and OmpLA into LUVs that contain PG or a small amount of PE (20%), but only at high pH (34,36). Furthermore, even in the presence of BamA, the assembly of OMPs into liposomes composed purely of neutral PC lipids was faster and more efficient, and BamA relieved the inhibitory effect of lipid head groups on the assembly of some proteins more effectively than others (34).…”
Section: Discussionmentioning
confidence: 99%
“…In the second assay we evaluated the orientation of the Bam complex using a tryptic digest. Previous work has shown that when BamA molecules insert into liposomes in an inside-out orientation (i.e., with their POTRA domains exposed on the surface), trypsin treatment generates a ~43 kD species (BamA*) that corresponds to the transmembrane β-barrel (36). We also expected that trypsin would digest Bam complex lipoproteins that are bound to surface exposed POTRA domains.…”
Section: Effective Reconstitution Of the Bam Complex Into Synthetic Lmentioning
confidence: 90%
See 3 more Smart Citations